A simulation study of the Japanese bō - Dong, Jonathan; Saley, Mohammed; Davies, Ian (Sage, 2013)
A study on various aspects of the Japanese bo including the most effective way to hold a bo to strike an object, the region along the length of the bo to impact an object, and the best method of resisting an impact were studied with the aid of finite element analysis (FEA). The results offer a very interesting scientific insight into the Japanese bo, which is very useful for improving the techniques of using the bo to one’s advantage, and improving the design of the Japanese bo.